Pengaruh Knowledge Sharing Factor Terhadap Keberlanjutan Penggunaan E-Learning Pasca Covid-19: The Influence of Knowledge Sharing Factors on the Continuity of Using E-Learning Post-Covid-19 - Ariyanti, Putri; Ditha Tania, Ken; Wedhasmara, Ari; Meiriza, Allsela (AI Society & STMIK Indonesia, 2023)
E-learning includes learning methods that use information technology and can be accessed via the internet, making it possible to learn remotely without face-to-face meetings. E-learning functions to implement knowledge management practices, especially in sharing knowledge. Studies on various knowledge-sharing factors influencing the adoption of e-learning in the post-pandemic context are still limited in the existing literature. Therefore, this study has the objective of developing an Expectation Confirmation Model by taking into account the factors of knowledge sharing (communication openness, personal trust, sharing motivation, use of technology, and perceptions of ease of use of technology) to test the viability of using e-learning, especially at Srivijaya University. This study uses the Partial Least Squares Structural Equation Modeling (PLS-SEM) method to test the validity of the developed model. Study data was collected from active students at Sriwijaya University who used or are currently using e-learning in lectures. The results of this study show that knowledge sharing factors, including openness of communication, personal trust, motivation to share, usefulness of technology, and perceived ease of use of technology, are important factors in determining the continued use of e-learning services at Sriwijaya University.